Essentials of Strategic Management: Effective Formulation and Execution of Strategy in the Era of Sustainability - Wunder, Thomas (Schäffer-Poeschel, 2023)
Written in English, this practice-oriented textbook covers all stages of the strategy process. Besides strategic analysis, strategy formulation, and business model innovation, the true challenges of strategic management will also be explained in detail: strategy execution and transformation. The context of strategy is currently experiencing radical changes in the world economy, planetary health, and socio-political foundations. In the era of sustainability, corporate leaders need to rethink their strategic management approach to effectively deal with these new and disruptive market situations. Sustainable strategizing is considered essential for future-proofing today's enterprises, transforming markets, and leading the way toward a sustainable future for both business and society. As a response to these developments, this updated and expanded edition continues to present the essentials of contemporary strategic management, but it also identifies, explores, and integrates ecological and social sustainability considerations to a great extent. As a result, key concepts of sustainable strategizing from mindsets, impact, materiality, and purpose to business cases, sustainable business models, regeneration, and transformation have been embedded and enhanced in the entire book. Other advancements are in the areas of dynamic capabilities, organizational ambidexterity, open strategy, the business ecosystem perspective, and strategic control. - Including a wealth of real-life strategy practice examples and strategic snapshots - Including a hands-on "strategy workout", exercises and review questions for students - Including teaching aids for lecturers In summary, students and practitioners will find many insights that will assist them in adding value to their organizations and society during the turbulent years ahead.